Evaluation of the effect of prostate volume change on tumor control probability in LDR brachytherapy - Knaup, Courtney; Mavroidis, Panayiotis; Stathakis, Sotirios; Smith, Mark; Swanson, Gregory; Papanikolaou, Niko (Journal of Contemporary Brachytherapy, 2011)
Purpose : This study evaluates low dose-rate brachytherapy (LDR) prostate plans to determine the biological effect of dose degradation due to prostate volume changes. Material and methods : In this study, 39 patients were evaluated. Pre-implant prostate volume was determined using ultrasound. These images were used with the treatment planning system (Nucletron Spot Pro 3.1 ® ) to create treatment plans using 103 Pd seeds. Following the implant, patients were imaged using CT for post-implant dosimetry. From the pre and post-implant DVHs, the biologically equivalent dose and the tumor control probability (TCP) were determined using the biologically effective uniform dose. The model used RBE = 1.75 and α/β = 2 Gy. Results: The prostate volume changed between pre and post implant image sets ranged from –8% to 110%. TCP and the mean dose were reduced up to 21% and 56%, respectively. TCP is observed to decrease as the mean dose decreases to the prostate. The post-implant tumor dose was generally observed to decrease, compared to the planned dose. A critical uniform dose of 130 Gy was established. Below this dose, TCP begins to fall-off. It was also determined that patients with a small prostates were more likely to suffer TCP decrease. Conclusions : The biological effect of post operative prostate growth due to operative trauma in LDR was evaluated using the concept. The post-implant dose was lower than the planned dose due to an increase of prostate volume post-implant. A critical uniform dose of 130 Gy was determined, below which TCP begun to decline.